Prevalence of Smoking among Health Workers and Effectiveness of Instructional Booklet concerning Risks of Smoking on Health Workers′ Knowledge in Baghdad Teaching Hospital - Yasir, Ahmed; Hassan, Huda Baker Hassan (Iraqi National Journal of Nursing Specialties, 2021)
Objective(s): The present study aims at assessing the prevalence of smoking among health workers in Baghdad Teaching Hospital and to find out the effectiveness of instructional booklet concerning risk of smoking on health workers′ knowledge in hospital. Methodology: A pre-experimental design study was conducted from 1st of October 2019 to 17th of March 2020. A non-probability sample consists of (500) participant (343 non-smokers and 157 smokers) from (1500) health workers in Baghdad Teaching Hospital, they included the physicians, nurses, pharmacists, physiotherapists, Laboratory Technicians, Medical Assistants. A questionnaire is constructed to evaluate the effectiveness of instructional booklet on health workers’ knowledge about risks of smoking which consists of (33) items. Reliability of the questionnaire is determined through the use of internal consistency reliability and the computation of Cronbach Alpha Correlation Coefficient which is equal to (0.905) and the content validity of the questionnaire is determined through a panel of experts. Results: The results of the study show that there is improvement of smokers’ knowledge concerning the effect of smoking on personal health status which is (50.9%), high percent of them not have enough knowledge at pretest while the improved their knowledge at posttest to (81.6%), and their knowledge about risk of smoking on hospital environment is improved from (51.6%) at pretest to (86.38%) at posttest, and there is a highly significant between the effectiveness of the instructional booklet and health workers’ knowledge about the risk of smoking on personal health at P ≤ 0.05 level.Recommendations: The study recommends that extensive and comprehensive studies, at the national level, could be conducted to improve the knowledge of health workers regarding the risks of smoking to human health and environment, and work to apply the penal code to the smokers inside hospitals and health institutions.